Long-acting reversible contraception utilization and associated factors among women in extended postpartum period in southern Ethiopia - Yibeltal Mesfin; Abraham Wallelign (BMC, 2021)
Abstract Background Postpartum long-acting reversible contraceptive is important to prevent unintended and closed spaced pregnancy following the first 12 months of childbirth. Few data were available on postpartum long-acting reversible contraceptive use in Ethiopia. So, this study aimed to assess the long-acting reversible contraception use and associated factors among women who gave birth in the last 12 months. Methods A community-based cross-sectional study was conducted from October 1st to November 2019. Systematic random sampling was applied to recruit a total of 416 study participants. Data were collected using a structured questionnaire. Data were entered using Epidata 4.6 and exported to SPSS version 25 for analysis. P-value < 0.05 with 95% confidence interval (CI) used to declare statistical significance. Result In this study, long acting contraceptive utilization among women in the extended postpartum period was 22.6%. Maternal age ≤ 24 years (AOR = 3.7, 95% CI: 1.5, 8.9), being married (AOR =3.5 95% CI: (1.17-10.28)), menses resumption (AOR = 4.9 95% CI: (2.92, 8.20)), sexual intercourse resumption (AOR = 7.1 95% CI: (4.03, 12.56)) and received postpartum family planning counseling (AOR = 3.2 95% (1.95, 5.28)) were the factors associated with Long-acting reversible contraception use. Conclusion This finding showed postpartum women's long-acting reversible contraceptive use during the extended postpartum period was low. The factors significantly associated with extended postpartum modern contraceptive use were women's age, being married, menses resumption, sexual intercourse resumption, and got postnatal family planning counseling. Strengthening Antenatal and postnatal counseling of postpartum family planning would improve long-acting reversible contraception use.